Teaching Vocabulary Using Fly Swatter Game at the Seventh Graders of Secondary School - Tiara Dwi Saputri (The Study Program of English Education of Palangka Raya University, 2022)
Vocabulary is one of the important elements in learning English. In fact, many students still face difficulties in mastering English vocabulary. This research is about to find out the effect of teaching vocabulary using Fly Swattter game at the seventh graders of secondary school. The method used in this research was a quasi-experiment by using one group pretest and posttest design. For the sample, the researcher took 32 students of the seventh grade of MTs Nurul Hidayah Mintin at Pulang Pisau Regency in the Central Kalimantan Province. Test and questionnaire were instruments used by the researcher to collect the data needed. The result shows that there is a significant effect of teaching English vocabulary using Fly Swatter game. This is also supported by students’ positive responses from questionnaire given. Therefore, the game has succeeded in improving students’ vocabulary of English.